Hearing results in patients undergoing canal wall down mastoidectomy with type III tympanoplasty - Öçalan, Ramazan; Ceyda Akın Öçalan, Fatma; Genç, Selahattin; Titiz, Ali; Ünal, Adnan (ENT Updates, 2013)
Objective: Preoperative and postoperative hearing results were compared in patients undergoing hearing reconstruction through open mastoidectomy with type III tympanoplasty method in our center. Methods: A total of 46 patients with chronic suppurative otitis media, who had undergone ossicular chain reconstruction by type III tympanoplasty with canal wall down mastoidectomy (CWDM) operation between January 2005 and 2009 were enrolled in the trial. The preoperative status of ossicular chain, the reconstruction methods on the ossicles, as well as the materials used in the reconstruction and the presence of stapes superstructure were recorded. Postoperative hearing gain of patients was evaluated by pure tone audiometry on an average of 6th months following surgery. Results: Among enrolled patients, 18 were females (39%) and 28 were males (61%). In 30 patients (65%), cholesteatoma was seen to have extended to the attic, antrum, supratubal recess and sinus tympani, while in 16 cases, cholesteatoma was determined to have partly invaded the mastoid cavity and mesotympanum. A polypoid tissue, arising from mucosa of middle ear and sagging into the external ear canal was detected in 6 patients (13%). While the preoperative and postoperative mean air-bone gaps were determined as 33.96 dB and 28.21dB, respectively. Preoperative and postoperative audiological examinations revealed an air-bone gap of £25 dB in 26.1 and 47.8% of the cases respectively. Conclusion: Type III tympanoplasty operation with canal wall down mastoidectomy provides eradication of the disease with cholesteatoma and enables reconstruction of hearing.